(untitled) (American Journal of Islam and Society, 1996)
The Islamization of Knowledge movement is gaining steady momentum among Muslim scholars. Efforts are being made to examine different academic disciplines from an Islamic perspective, which is a clear indication of the growing desire to develop a new hework of knowledge. One result of this is the above-mentioned conference, which was organized by the Society for the Advancement of Muslim Psychology (SAMP), Pakistan, with the collaboration of the International Institute of Islamic Thought (IIIT), Pakistan. SAMP was founded by Syed Azhar Ali Rizvi, chairman of the Department of Psychology, Government College, Lahore, some ten years ago. Among the society’s objectives are: to promote the cause of Muslim psychology as a basic as well as an applied science, and of Muslim psychologists as academicians and professionals working for the welfare of the individual and the society; to explore ways and means of improving the quality of training, research, and professional competence of Muslim psychologists; and to apply the teachings of the Qur’an and hadith and the interpretations of eminent Muslims thinkers in the diagnosis, treatment, and rehabilitation of those who need psychological care ...